The Influence of Video Tutorials on Learning Outcomes of Islamic Religion in Class X Students in Online Business and Marketing Smk Negeri 2 Sidenreng Rappang - Idharul Haq; Usman M; Abd Kahar; Hermansyah, Sam; Muhammad Hanafi (International Journal of Sustainable Applied Sciences, 2023)
This use method quantitative And type study experiment which aim For test influence video tutorial on the learning outcomes of Islamic Religion for class X Online Business and Marketing SMK Negeri 2 Sidenreng Rappang. Population research, namely all Class X Online Business and Marketing SMK Negeri 2 Sidenreng Rappang and the sample taken was 37 people class X Online Business and Marketing students at SMK Negeri 2 Sidenreng Rappang and use Arikunto's opinion. Variable on study this there is 2, which first that is variable free that is the effect of using video tutorials (x) and the two dependent variables namely Islamic Religion learning outcomes for Class X students of Online Business and marketing at SMK Negeri 2 Sidenreng Rappang (y). This research was conducted at SMK Negeri 2 Sidenreng Rappang. Based on the results of data analysis, it was obtained that the value of X = 86.5 > the value of Y = 54.05 so that it can be seen that there is influence Video tutorial on learning outcomes of Islamic Religion for Class X students of Online Business and Marketing at SMK Negeri 2 Sidenreng Rappang. Results study This concluded that there is Influence Video tutorial on learning outcomes of Islamic Religion for Class X students of Online Business and Marketing at SMK Negeri 2 Sidenreng Rappang. Matter This show that hypothesis Work Which state There is Influence Video tutorial on learning outcomes of Islamic Religion Class X Students Online Business and Marketing SMK Negeri 2 Sidenreng Rappang , accepted.